STUDI ANALISIS PERAN NADZIR DALAM PENGELOLAAN WAKAF PRODUKTIF DI DESA MOJOREJO KECAMATAN JUNREJO KOTA BATU - Farhana Nur lailita; Ach. Faisol; Dzulfikar Rodafi (Jurnal Hikmatina, 2021)
This study discusses about the role of nadzir wakaf in terms of positive law and Islamic fiqh. As well as how to manage wakaf asset and the result of that wakaf asset This study was conducted to fulfil one of the requirements in completing the undergraduate program (S-1) islamic family law. Qualitative method was used in this study with asociological approach and the instruments were used there were interview and documentation. The result of this study conclude that the role of nadzir in managing wakaf property is very important, because nadzir is an important part of the management of productive wakaf, and the way of managing it was done by agriculture that the result then given completely to the mosque of Miftakhul Jannah for the prosperity of the mosque. Kata Kunci : Wakaf, Peran Nadzir, pengelolaan wakaf produktif